1938
DOI: 10.1113/jphysiol.1938.sp003680
|View full text |Cite
|
Sign up to set email alerts
|

The blood‐pressure raising secretion of the ischaemic kidney

Abstract: THE co-existence of arterial hypertension and renal lesions has been observed for a long time. This fact has induced many investigators to attempt the production of arterial hypertension by experimental modification of the kidney. The methods used have been numerous and varied, e.g. surgical removal of part of the kidney, ligature of the renal artery or some of its branches, reduction of the calibre of the renal vein, ligature of the ureter, multiple emboli of the kidney, irradiation of the kidney, toxic nephr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
19
0

Year Published

1939
1939
2012
2012

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 83 publications
(20 citation statements)
references
References 2 publications
0
19
0
Order By: Relevance
“…Later on, in1934, Goldblatt et al, found that hypertension in animal models induced by renal ischemia caused a release of vasoconstrictor substance (Goldblatt, Lynch, Hanzal, & Summerville, 1934). After that, two independent groups were the first to report the end product of this cascade in 1939 and they named it as "Hypertensin" (Fasciolo, Houssay, & Taquini, 1938) and "Angiotonin" (Page, 1939), separately. Soon after, the two groups agreed on a common nomenclature of the vasopressor end product of renin activity as (angiotensin) (BraunMenendez & Page, 1958).…”
Section: Introduction Renin Angiotensin System (Ras)mentioning
confidence: 99%
“…Later on, in1934, Goldblatt et al, found that hypertension in animal models induced by renal ischemia caused a release of vasoconstrictor substance (Goldblatt, Lynch, Hanzal, & Summerville, 1934). After that, two independent groups were the first to report the end product of this cascade in 1939 and they named it as "Hypertensin" (Fasciolo, Houssay, & Taquini, 1938) and "Angiotonin" (Page, 1939), separately. Soon after, the two groups agreed on a common nomenclature of the vasopressor end product of renin activity as (angiotensin) (BraunMenendez & Page, 1958).…”
Section: Introduction Renin Angiotensin System (Ras)mentioning
confidence: 99%
“…27 It became necessary to establish the nature of this compound and to characterize, purify, and isolate it to identify its chemical structure.…”
mentioning
confidence: 99%
“…The main cell type noted in the protective renomedullary transplants had the microscopic characteristics of the lipid-containing interstitial cells. These cells occurred INTRODUCTION An antihypertensive function of the normal kidney was proposed in relation to the Goldblatt experiment (1)(2)(3)(4)(5).…”
mentioning
confidence: 99%